Personal Data Protection Governance in the Asia Pacific Region: A Review of the Scope, Effectiveness, and Legal Challenges - Heppy Endah Palupy; Ronald Nawing; Susi Susantijo (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
The rapid expansion of personal data protection legislation across the Asia-Pacific region has generated a diverse regulatory landscape, yet existing scholarship remains fragmented, largely focusing on individual jurisdictions and offering limited comparative analysis of how different legal frameworks influence privacy protection outcomes. This study addresses that gap by systematically mapping and synthesizing literature on personal data protection governance across Asia-Pacific jurisdictions during the post-GDPR period (2016–2025). Employing a scoping review methodology based on Arksey and O’Malley’s framework and guided by PRISMA-ScR standards, the study analyzes 61 publications indexed in Scopus. The findings reveal a pattern of “principled divergence,” whereby jurisdictions selectively adapt international privacy standards rather than uniformly transplanting GDPR-based models. Three regulatory clusters emerged: developed jurisdictions with mature governance frameworks, transitional jurisdictions experiencing implementation gaps, and emerging jurisdictions facing institutional and regulatory capacity constraints. The study further finds that regulatory effectiveness depends less on legal stringency than on the interaction between institutional capacity, accountability mechanisms, enforcement effectiveness, technological readiness, and contextual regulatory adaptation. From a legal perspective, the findings demonstrate that variations in privacy protection outcomes are closely linked to differing constitutional understandings of privacy rights, state obligations, and regulatory governance. The study contributes to comparative privacy law, digital constitutionalism, and regulatory governance theory by explaining how legal frameworks operate within diverse socio-legal environments. Practically, the findings provide guidance for policymakers seeking to strengthen data protection governance through institutional capacity-building, regulatory interoperability, and context-sensitive implementation strategies rather than relying solely on legislative harmonization.